An Analytical Model of Interest Rate Differentials and Different Default Recoveries - Yawitz, Jess B. (Journal of Financial and Quantitative Analysis, 1977)
In this paper we have extended the Bierman-Hass model to include the effect of a second parameter, the terms of settlement in the event of default. The addition of this second factor was found to not alter the independence between a bond's risk differential and its maturity. Our analysis of the required risk differential for various borrower credit characteristics demonstrates the tradeoff between p and γ. Throughout, we have assumed the loan size does not affect p or γ.